Caribbean software for natural products chemistry - Lancashire, Robert (Technical Centre for Agricultural and Rural Cooperation, 2005)
Robert Lancashire tells the success story of the JCAMP-DX Data Viewer, a computer program developed in Jamaica that is now being used by organic chemists worldwide